The Effect of Strategic Agility Dimensions in Enhancing The Immune System: A Survey Of The Opinions Of Sample in The National Insurance Company - kurtany, L. Firas A. Mohammed. AL; Alan , L. Mohammed I.T.; msoodi , L. Amer RashidAanid AL; Kadum, L. Juliet (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to identify the correlations and influence of the strategic agility dimensions, which were represented by (strategic sensitivity, collective commitment (unity of command), and the flow of strategic resources) in enhancing the ability of the regulatory immune system through its basic dimensions represented by (central immune system, specialized immune system, and system Immunity to the limbs) by studying these variables and revealing any of these dimensions has a direct impact on enhancing the ability of the immune regulatory system in the researched company, as the research used to measure these variables a questionnaire prepared based on previous studies, as well as adapting the paragraphs in proportion to the current research. As the research community consisted of (75) individuals who occupy administrative positions (as branch manager, head of department and division official) in the National General Insurance Company. A random sample of (62) individuals was chosen to represent the research community, and the data was processed using a set of statistical methods using a program Spss version 26, as it has been proven that there is a direct relationship to the dimensions of strategic sensitivity and the flow of strategic resources more than the effect of collective commitment, as the research suggests, reformulating laws, organizational rules of behavior and the compensation system that would enhance the ability of the immune system to confront internal organizational diseases.